Pharmacists’ knowledge, Attitude and Involvement in Palliative Care in Selected Tertiary Hospitals in Southwestern Nigeria (2019)
Background: The growing number of people living with life-limiting illness is a global health concern. This study therefore aimed to explore the involvement of pharmacists in selected tertiary hospitals in Nigeria in palliative care (PC). It also sought to evaluate their knowledge and attitude to PC as well as factors that hinder pharmacists’ participation in PC. Method: Questionnaire-guided survey among pharmacists working in three-tertiary hospitals in southwestern Nigeria. The self-administered questionnaire comprised 18-item general knowledge questions related to PC, attitude statements with 5-point Likert-scale options and question-items that clarify extent of involvement in PC and barriers to participation. Overall score by pharmacists in the knowledge and attitude domains developed for the purpose of this study was assigned into binary categories of “adequate” and “inadequate” knowledge (score > 75% versus≤75%), as well as “positive” and “negative” attitude (ranked score > 75% versus≤75%), respectively. Descriptive statistics, Mann-Whitney-U and Kruskal-Wallis tests were used for analysis at p < 0.05. Results: All the 110 pharmacists enrolled responded to the questionnaire, given a response rate of 100%. Overall, our study showed that 23(21.1%) had adequate general knowledge in PC, while 14(12.8%) demonstrated positive attitude, with 45(41.3%) who enjoyed working in PC. Counselling on therapy adherence (100;90.9%) was the most frequently engaged activity by pharmacists; attending clinical meetings to advise health team members (45;40.9%) and giving educational sessions (47;42.7%) were largely cited as occasionally performed duties, while patient home visit was mostly cited (60;54.5%) as a duty not done at all. Pharmacists’ unawareness of their need in PC (86;79.6%) was a major factor hindering participation, while pharmacists with PC training significantly felt more relaxed around people receiving PC compared to those without training (p = 0.003). Conclusion: Hospital pharmacists in selected tertiary care institutions demonstrate inadequate knowledge, as well as negative attitude towards PC. Also, extent of involvement in core PC service is generally low, with pharmacists’ unawareness of their need in PC constituting a major barrier. Thus, a need for inclusion of PC concept into pharmacy education curriculum, while mandatory professional development programme for pharmacists shouldnalso incorporate aspects detailing fundamental principles of PC, in order to bridge the knowledge and practice gaps.